Interstitial and Intracavitary Thermoradiotherapy - Seegenschmiedt, M. Heinrich (Medical Radiology, Diagnostic Imaging and Radiation Oncology., 1993)
While hyperthermia has long been used within radiation oncology, the highly promising new techniques of interstitial and intracavitary hyperthermia are generally less well known. The considerable advantage of "internal" application of combined radiotherapy and hyperthermia is thata high degree of therapeutic efficacy can be achieved within a limited target volume while sparing surrounding structures from side-effects. It is therefore no surprise that the past decade has witnessed a dramatic increasein basic research into internal heating techniques, together with rapid technical development and expansion of clinical applications. This timely volume summarizes all essential biological aspects of heat interaction with radiotherapy, presents the technical state of the art, and analyzes the clinical results achieved with application of interstitial and intracavitary thermo-radiotherapy for tumors of a variety of sites. Treatment control and planning are given full consideration in a separate section, as too are special clinical applications. The final section discusses the design and performance of multicenter clinical trials. This book, written by recognized experts, will be of great valueto the theoretical researcher, the oncological practitioner, and specialistsin all related theoretical and clinical sciences of oncology.